The Internal Clock: A Manifestation of a Misguided Mechanistic View of Causation? - Eckard, Matthew L.; Lattal, Kennon A. (Perspectives on behavior science, 2020)
Across various subfields within psychology, mechanistic causation is invoked regularly. When the temporal contiguity of the typical cause–effect relation is violated, mechanistic causation often assigns causal roles to mediating hypothetical constructs to account for observed effects. Two primary consequences of mechanistic causation are that 1) the proposed hypothetical constructs add what many behavior analysts consider an unnecessary step in the causal chain, and 2) these constructs then become the focus of study thereafter diverting attention from more accessible “causes.” Constructs do not contribute directly to determining the control of behavior; thus, their reification as “causes” often distracts from variables that do fulfill a causal role. In this review, these consequences are discussed in relation to theories of interval timing proposing an internal clock. Not only has this clock been said to be a cause of behavior in experiments on temporally regulated behavior, but also the clock itself has been a frequent subject of study within the timing literature. Despite descriptive accounts of this sort initially serving a heuristic function for model development, the promotion from descriptive aid to causal factor has the potential to limit much of the heuristic value that mechanistic models of causation can provide to the analysis of behavior. Problems related to construct reification are less likely to be at issue when functional relations and the processes of establishing such behavior are emphasized as alternatives to mechanistic causation alone.